Annual benthic metabolism and organic carbon fluxes in a semi-enclosed Mediterranean bay dominated by the macroalgae Caulerpa prolifera - Ruiz-Halpern, Sergio; Vaquer-Sunyer, Raquel; Duarte, Carlos M. (Frontiers in Marine Science, 2014)
Coastal areas play an important role on carbon cycling. Elucidating the dynamics on the production, transport and fate of organic carbon is relevant to gain a better understanding of the role coastal areas play in the global carbon budget. Here, we assess the metabolic status and associated organic carbon fluxes of a semi-enclosed Mediterranean bay supporting a meadow of Caulerpa prolifera. We test whether the EDOC pool is a significant component of the organic carbon pool and associated fluxes in this ecosystem. The Bay of Portocolom was in net metabolic balance on a yearly basis, but heterotrophic during the summer months. Community respiration (CR) was positively correlated to C. prolifera biomass, while net community production (NCP) had a negative correlation. The benthic compartment represented, on average, 72.6 ± 5.2 % of CR and 86.8 ± 4.5 % of gross primary production (GPP). Dissolved organic carbon (DOC) production peaked in summer and was always positive, with the incubations performed in the dark almost doubling the flux of those performed in the light. Exchangeable dissolved organic carbon (EDOC), however, oscillated between production and uptake, being completely recycled within the system and representing around 14% of the DOC flux. The pools of bottom and surface DOC were high for an oligotrophic environment, and were positively correlated to the pool of EDOC. Thus, despite being in metabolic balance, this ecosystem acted as a conduit for organic carbon (OC), as it is able to export OC to adjacent areas derived from allochtonous inputs during heterotrophic conditions. These inputs likely come from groundwater discharge, human activity in the watershed, delivered to the sediments through the high capacity of C. prolifera to remove particles from the water column, and from the air-water exchange of EDOC, demonstrating that these communities are a major contributor to the cycling of OC in coastal embayments.